2008
DOI: 10.1089/jir.2007.0057
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Expression of the IL-31 Receptor in Bronchial and Alveolar Epithelial Cells, Pulmonary Fibroblasts, and Pulmonary Macrophages

Abstract: Interleukin-31 (IL-31), an IL-6 cytokine family member, is proposed to play a role in animal models of airway hyperreactivity. It is produced by activated T cells and signals via a heterodimeric receptor complex composed of IL-31Ralpha and OSMRbeta. Only low levels of IL-31Ralpha expression have been demonstrated in pulmonary epithelial cell lines, however, and little is known about the ability to regulate its expression and signaling. Therefore, primary cultures of human bronchial and alveolar epithelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…It is likely that additional signals from different cells modulate IL-31 activity in cell proliferation (22). Although recent studies have demonstrated that IL-31 is effective in suppressing the proliferation of lung epithelial cells (48,49). Furthermore it is known that IL-31 stimulates STAT-3 and STAT-5 (18,22), by which some cytokines are involved in haematopoiesis (50).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that additional signals from different cells modulate IL-31 activity in cell proliferation (22). Although recent studies have demonstrated that IL-31 is effective in suppressing the proliferation of lung epithelial cells (48,49). Furthermore it is known that IL-31 stimulates STAT-3 and STAT-5 (18,22), by which some cytokines are involved in haematopoiesis (50).…”
Section: Discussionmentioning
confidence: 99%
“…IFNg stimulation results in a STAT1-dependent increase in IL-31RA transcription in monocytes, macrophages, dendritic cells, keratinocytes and dermal microvascular endothelial cells [39,131,[135][136][137][138]. Promoter analysis and chromatin IP assays demonstrated STAT1 binding to the IL-31RA promoter [138].…”
Section: Cytokine-receptor Interactionmentioning
confidence: 98%
“…Absence of the type II IL-4 receptor attenuated the expression of IL-31RA in vivo during allergic asthma [139]. In primary cultures and established lines of epithelial cells IL-31RA mRNA was induced by TGFb [135]. A particular high expression of IL-31RA and OSMRb was found in small diameter dorsal root ganglia (DRG) neurons and repeated administration of IL-31 resulted in up-regulation of both receptors in DRG and intensified long-lasting scratching behavior in treated mice [140,141].…”
Section: Cytokine-receptor Interactionmentioning
confidence: 99%
“…Interleukin-31Rα, although often classified as a β subunit, can only transduce signal when combined with another β subunit. 52 The β subunits may combine with another β subunit or with the α subunits of selected IL-6 cytokines to form dimeric or multi-meric complexes. 70,81 The shared subunit for the IL-6 cytokines, with the exception of IL-31, is gp130.…”
Section: Interleukin-6 Type Cytokine and Receptor Pathophysiologymentioning
confidence: 99%
“…Interleukin-31 signals via IL-31Rα/OSMRβ. 52 Finally, CNTF and CLC signal via the CNTFRa/LIFR/gp130 complex. 70 …”
Section: Interleukin-6 Type Cytokine and Receptor Pathophysiologymentioning
confidence: 99%